2015
DOI: 10.1371/journal.pone.0118329
|View full text |Cite
|
Sign up to set email alerts
|

Women Favour Dyadic Relationships, but Men Prefer Clubs: Cross-Cultural Evidence from Social Networking

Abstract: The ability to create lasting, trust-based friendships makes it possible for humans to form large and coherent groups. The recent literature on the evolution of sociality and on the network dynamics of human societies suggests that large human groups have a layered structure generated by emotionally supported social relationships. There are also gender differences in adult social style which may involve different trade-offs between the quantity and quality of friendships. Although many have suggested that fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(94 citation statements)
references
References 61 publications
5
87
1
1
Order By: Relevance
“…Women spend more time discussing feelings and personal information and their friendships tend to be dyadic in nature, which does not allow for substitute partners if relationships break down (Benenson & Christakos, 2003;David-Barrett et al, 2015;Vigil, 2007). This focus on exclusive friendships characterised by information sharing may provide a context for specific types of manipulation to take place.…”
Section: Introductionmentioning
confidence: 99%
“…Women spend more time discussing feelings and personal information and their friendships tend to be dyadic in nature, which does not allow for substitute partners if relationships break down (Benenson & Christakos, 2003;David-Barrett et al, 2015;Vigil, 2007). This focus on exclusive friendships characterised by information sharing may provide a context for specific types of manipulation to take place.…”
Section: Introductionmentioning
confidence: 99%
“…Although gender has not shown significant effects on friendship network, the same-gender dyads or triads are not explored in this study. Previous studies showed that women's dyads differ from men's and that women prefer dyads while men prefer larger, all-male cliques (David-Barrett et al 2015). Because there is a small number of males in this study, differentiation of the same-gender and the opposite gender relationships is not justifiable.…”
Section: Discussionmentioning
confidence: 76%
“…We used a recently published Profile Picture dataset which focused on gender differences in close friendship (David-- Barrett et al, 2015). This dataset contains the profile picture type of 309 individuals and all their altogether 111,863 friends.…”
Section: Data Methods and Hypothesesmentioning
confidence: 99%
“…The dataset was constructed the following way (David-- Barrett et al, 2015). First, the coders used random search terms to select 309 users of Facebook, all of whom share their friends publicly.…”
Section: Data Methods and Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation